Mechanical Properties Enhancement of Al-Si-Cu-Fe Alloy Through Aging Treatment Variations - Moch Iqbal Zaelana Muttahar; Shinta Virdhian; Purbaja Adi Putra; Dagus Resmana Djuanda; Eva Afrilinda; Amsal Genesar (Metalurgi, 2020)
Al-Si alloys are being widely used as main engine components replacing iron in several parts in the automotive industry. Some of its mechanical properties were a reference in its alloy utilization. In this research, the heat treatment carried out on the specimen included solid solution treatment and the artificial aging process for aluminium alloys. Test pieces were heated on the furnace with a solid solution treatment process at 540 ° C with holding time around 5 hours and quenched at 60 °C with water quenchant, followed by 3 different aging treatment which included single-stage aging, artificial aging with pre-aged, and double stage aging. Tests carried out by hardness test, tensile strength test, impact test, metallographic and Scanning Electron Microscopy-Energy Dispersive Spectroscopy (SEM-EDS) observations. The results of this research showed the differences in phase constituent and morphology microconstituents due to variations of aging. The difference of each treatment could be seen in the morphology of the precipitate that is dispersed, rounded and needle-like shaped, this phase can influence the mechanical properties of Al-Si-Cu alloys. The results of mechanical testing show the highest hardness was obtained by double stage aging treatment 161.27 HRB. The highest tensile strength occurs in specimens with a single-stage aging treatment of 202.56 MPa. The highest impact resistance occurred in samples with the pre-aging treatment of 18.6 J.